Exploring the 4D printing linked bio-smart materials in dentistry: a concise overview - Aafreen M, Maajida; Cholan, Priyanka K.; Ilango, Paavai; Parthasarathy, Harinath; Tadepalli, Anupama; Ramachandran, Lakshmi (Frontiers in Dental Medicine, 2025)
4D printing advances traditional 3D printing by incorporating the dimension of time, enabling stimuli-responsive shape or behavior changes. Bio-smart materials, crucial to this technology, enable programmable transformations with significant potential in biomechanics and dentistry. This review explores the use of smart materials and stimuli in 4D printing, emphasizing dental applications.A comprehensive search across EMBASE, Web of Science, MEDLINE, Cochrane Library and clinical trial registries identified 154 articles on 4D printing technologies, biomaterials, and stimuli relevant to dental applications. Of these, 84 were pertinent to the review's objective, with 25 specifically focused on 4D printing and various smart materials. The review highlights biomaterials engineered for programmable responses, such as shape memory polymers, shape memory elastomers, responsive inks, and hydrogels. These materials enable the creation of structures that can adapt, self-assemble, or respond to stimuli like temperature, moisture, or pH levels. In dentistry, these capabilities show potential for applications in orthodontics, implants, and tissue engineering.The integration of 4D printing and bio-smart materials has the potential to transform dentistry by creating adaptive, time-responsive structures. This technology enables personalized, precise, and minimally invasive treatments, addressing complex biomechanical challenges in dental care.